Between principles and pragmatism - primary healthcare and social services professionals' experiences and perceptions of self-care for older adults with home care: a qualitative study - Ing-Mari Dohrn; Åsa von Berens; Christina B. Olsson; Elisabeth Rydwik; Elin Jakobsson; Lina Palmlöf (Taylor & Francis Group, 2024)
Objective To explore the experiences of healthcare and social services professionals and their perceptions of using Certificate for self-care with support (CSS) for preventive self-care for older adults with home care, including the CSS process and collaborations between primary healthcare and social services.Design An inductive qualitative study including seven focus group interviews analyzed with reflexive thematic analysis.Setting and subjects The study was conducted in the Stockholm Region 2022/23. In total, 23 informants were recruited from four key partners involved in the CSS process: professionals from primary care rehabilitation and primary healthcare, social services officers, and home care staff.Result The analyses resulted in five interconnected themes: 'Guidelines with scope for interpretation,' 'Support for self-care is needed, but complicated in practice,' 'To trust the other professions' competence,' 'There is a transfer of responsibility,' and 'Communication is key.' The overarching theme 'Principles or pragmatism for safe person-centered care,' anchoring the other themes, revealed a common goal of achieving safe and individualized care within available resources, but from two conflicting perspectives: the importance of following the process according to the guidelines or taking a more pragmatic approach.Conclusion This study highlights the need to establish structures facilitating safe self-care among frail groups, such as older persons dependent on home care. Our findings emphasize that the demarcation between, and responsibilities of, organizations need to be discussed and clarified to offer person-centered support. Comprehensible guidelines and functioning communication channels must be established so that all important perspectives can be heard, not least the patient's.